Karakteristik Morfologi Jenis-Jenis Mangrove di Kawasan Wisata Karosondaya Desa Sausu Tambu - Darise, Aswan A.; Isnainar, Isnainar; Febriawan, Aan; Febriani, Vita Indri; Buntu, Amalia; Mawaddah, Hayyatun (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to describe the observed morphological characteristics consisting of mangrove types or species, soil substrates, roots (root types, root modifications and root colors), stems (stem color, stem texture and diameter), leaves (leaf shape, leaf texture, leaf tips, leaf color and leaf length), fruits (fruit types and fruit shapes), flowers (colors and shapes) of true mangrove species in the Karosondaya tourist area of Sausu Tambu Village. This type of research is a descriptive type of research conducted by determining the research location by purposive sampling which is divided into 3 observation stations. Sampling was carried out by exploring and free collection. The results of the study showed that there were 11 mangrove species identified in the Karosondaya tourist area of Sausu Tambu village. The types of mangrove plants found consisted of Rhizophora apiculata (Blume), Rhizophora stylosa (Griffith), Ceriops decandra (Griff), Ceriops tagal (Perr) C.B. Rob, Ceriops zippeliana (Blume), Bruguiera gimnorhiza (L). Lam, Xylocarpus granatum (J. Keonig), Sonneratia alba (J.E.Smith), Sonneratia ovate (Backer), Avicennia germinans (L), Lumitzera rasemosa (Willd). With the dominant species being Rhizophora apiculata (Blume), Rhizophora stylosa (Griffith), Avicennia germinans (L), while the rare or rarely found species were Lumnitzera racemosa (Willd) and Ceriops tagal (Perr.) C.B. Rob.